Touch Dna as Forensic Aid: A Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Touch DNA technique which is being used in many advanced countries as a modern tool in criminal justice system. It is basically meant for acquiring genetic information from biological substances (cells released from epidermal surfaces) left on touched samples to establish it’s relatedness. It refers to recovery of traces of DNA from the biological cells released during the contact which is in a very low quantity, for further analysis and generation of a DNA profile of a person. Released dead cells are not visible to naked eyes and hence it is difficult to locate and recover successfully. DNA profiling from touched samples is difficult and hence require sensitive approach in recovery, extraction and amplification. Success of Touch DNA analysis, therefore, depends upon various factors like collection, sampling and preservation, removal of contaminations, quantification, amplification, analysis and interpretations. Various methods have been developed for the collection of Touch DNA over the time. Sophisticated kits and instrument and well equipped forensic laboratories help to provide concrete DNA profiles thus helping to the Criminal Justice System.